2008
DOI: 10.1080/07399330802089198
|View full text |Cite
|
Sign up to set email alerts
|

What Matters Most: An Investigation of Predictors of Perceived Stress Among Young Mothers in Khayelitsha

Abstract: Our purpose in the present study was to examine how two different sets of stressors, one representing the physical environment and the other representing the social environment, related to perceived stress among new mothers served by a health clinic in Khayelitsha, South Africa. We found that among the chronic urban poverty-environmental stressors related to water, housing, transportation, toileting, and lack of food, that lack of drinkable water in the home had the strongest correlation with perceived stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…We found inconclusive evidence that water carriage is associated with stress from quantitative data ( table 3 ) and strong evidence from qualitative data ( table 4 ). Two rigorous qualitative studies, 34 57 and one fair quality 36 and two poor quality 27 34 cross-sectional surveys, reported water carriage to be associated with stress ( table 7 ). In these studies, psychosocial distress was identified as an effect of water carriage by thematic analysis, and measured using three different questionnaires and by quantification of hair cortisol content as a biomarker for chronic stress.…”
Section: Resultsmentioning
confidence: 99%
“…We found inconclusive evidence that water carriage is associated with stress from quantitative data ( table 3 ) and strong evidence from qualitative data ( table 4 ). Two rigorous qualitative studies, 34 57 and one fair quality 36 and two poor quality 27 34 cross-sectional surveys, reported water carriage to be associated with stress ( table 7 ). In these studies, psychosocial distress was identified as an effect of water carriage by thematic analysis, and measured using three different questionnaires and by quantification of hair cortisol content as a biomarker for chronic stress.…”
Section: Resultsmentioning
confidence: 99%
“…[ 73 ] The belief and perception of the influence of stress on CVDs in SSA populations could however be related to experiences of psychosocial stressors arising out of urbanization and poverty. [ 74 , 75 ] Experiences of chronic poverty-related stressors, such as inadequate housing, sanitation, water, overcrowding, environmental conditions, low education and unemployment, are potent predictors of poor cardiovascular health. [ 76 78 ] Strategies to deal with perceived psychosocial stress among these populations, include smoking and alcohol consumption, which themselves are precursors of poor cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Khayelitsha is one of the largest such settlements in South Africa, with a population exceeding 1 million residents (Brunn and Wilson 2013) who are primarily Xhosa-speaking, black Africans living in informal housing (i.e., shacks) on unserviced land. Unemployment, food insecurity, and subsistence-level poverty rates are extremely high (BeLue et al 2008; Cooper et al 1991; Dewing et al 2013; Muzigaba and Puoane 2011; Pick and Obermeyer 1996; Venkataramani et al 2010). Khayelitsha leads all sub-districts of Cape Town in age-standardized mortality, with the leading causes being HIV/AIDS, homicide, and tuberculosis (Groenewald et al 2010).…”
Section: Methodsmentioning
confidence: 99%